The Use of Nano Bio Fusion Gingival Gel as Adjuvant Therapy in The Treatment of Periodontal Disease: A Literature Review - Olivia Nauli Komala; Luki Astuti (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: There are various types of adjuvant agents used in periodontal treatment, one of which is Nano Bio Fusion (NBF) Gingival Gel. Numerous studies have assessed the use of NBF gel in the treatment of periodontal disease. This paper attempts to review the literature on the efficacy of utilizing NBF gel to treat periodontal disease. Review: Nano-Bio Fusion Gingival Gel contains propolis extract in the form of nanoemulsion, vitamin C, vitamin E, sodium monofluorophosphate, aloe, and green tea extract. NBF gel is used for protection and prevention in various oral conditions, such as gingival and periodontal disease; ulcerated conditions, erosions, xerostomia, white lesions of the mucosa, denture stomatitis; mucosal protection after radiation therapy or chemotherapy; dry lips or cheilitis, lip inflammation; and post-surgical conditions such as tooth extraction, alveolitis, after implant placement, flap surgery, periodontal abscess treatment, and others. In eight studies, NBF gel was found to be effective in the treatment of periodontal disease. The parameters used were plaque index, papillary bleeding index, pocket depth, clinical attachment level, gingival index, pain perception, signs of inflammation, sulcular bleeding index, and colony forming unit. The best results were seen in the use of NBF gel after scaling. In comparison to other adjuvants, such as tetracycline fiber and hyaluronic acid (Gengigel), the results of the parameters obtained with NBF gel are not as excellent as those obtained with the other two substances. Conclusion: NBF gel can be an effective adjuvant treatment following scaling.